Stereological Analysis of Human Placenta in Cases of Placenta Previa in Comparison with Normally Implanted Controls - Z Heidari; N Sakhavar; H Mahmoudzadeh-Sagheb; T Ezazi-Bojnourdi (JRI, 2015)
Background: placenta previa (PP) is an obstetric complication that can affect maternal and fetal morbidity and mortality. Its prevalence is rising due to cesarean sections. There is no quantitative data of placenta in PP. In this study, quantitative parameters of placenta in cases with PP in comparison with normally implanted controls were investigated. Methods: In this quasi experimental study, placentas from pregnancies with PP and normally implanted controls (n=10) were obtained from women who underwent cesarean section. Three full-thickness columns of each placenta were sampled using systematic uniform random sampling (SURS). Columns were cut into slices and slices were sectioned with 4 μm thickness. SURS selected sections were stained by Masson’s trichrome. Stereological analysis was done on 8-10 SURS microscopic fields of each section. Absolute volume and volume density of chorionic villi, intervillous space, syncytiotrophoblast, fibrin and blood vessels in chorionic villi were estimated in both groups. Statistical analysis was done using Mann Whitney-U test and significant level was set at p<0.05. Results: There was a significant reduction in total volume and volume density of fibrin deposits on the surface of chorionic villi (p<0.05), and a significant increment in total volume and volume density of chorionic villous blood vessels in PP group in comparison with C group (p<0.05). Conclusion: Results showed that impairment in situation of implantation in PP can cause significant changes in the structure of placenta. These changes probably can be influential on the evolution and survival of fetus.